Stagnation Point Flow Past a Stretching Sheet in a Nanofluid with Slip Condition and Viscous Dissipation - Muhammad Khairul Anuar, Mohamed; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Anuar, Ishak (2014)
In this study, the numerical investigation of stagnation point flow past a stretching sheet in nanofluid with slip condition and viscous dissipations is considered. The governing equations for the model which is in non linear partial differential equations are first transformed to ordinary differential equation by using similarity transformation. Thisordinary differential equations are solved numerically by using the Runge-Kutta-Fehlberg method. Numerical solutions are obtained for the wall temperature, reduced Nusselt, Sherwood number and skin friction coefficient as well as the temperature profiles. The features of the flow and heat transfer characteristics for various values of the stretching parameter, Brownion and thermopherosis motion parameter, Eckert number, velocity slip parameter and thermal slip parameter are analyzed and discussed.